2006
DOI: 10.1117/12.680765
|View full text |Cite
|
Sign up to set email alerts
|

The complex optical response of arrays of aligned multiwalled carbon nanotubes

Abstract: The optical properties of periodic and nonperiodic arrays of aligned multiwalled carbon nanotubes are presented. Experimental analysis indicates a complex optical response that is attributed to both the individual carbon nanotube scatterers and also to the array ensembles. These studies indicate that by controlling the geometry and spacing of the arrays, it is possible to create structures that respond very strongly to specific wavelengths or bands of wavelengths. Structures such as these may form the basis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recently (Dresselhaus, 2004;Burke, Rutherglen and Yu, 2006;Gregorczyk et al, 2006;Wang et al, 2004) it has been shown that metallic MWCNTs as random or regular arrays are so reflective that they can be used as optical nanoantennas. Indeed, such effect can be predicted theoretically; however practical experimentations (Wang et al, 2004;Gregorczyk et al, 2006) have shown that complex optical responses can be obtained from periodic and nonperiodic arrays of MWCNTs as a result of controlling the geometry and spacing of the arrays, so that it is possible to create structures that respond very strongly to specific wavelengths or bands of wavelength. Finely tuned detectors that can respond to predetermined wavelength bands ranging from the ultraviolet to the infrared region.…”
Section: A Case Study -Flying At 0001c and Beyondmentioning
confidence: 99%
“…Recently (Dresselhaus, 2004;Burke, Rutherglen and Yu, 2006;Gregorczyk et al, 2006;Wang et al, 2004) it has been shown that metallic MWCNTs as random or regular arrays are so reflective that they can be used as optical nanoantennas. Indeed, such effect can be predicted theoretically; however practical experimentations (Wang et al, 2004;Gregorczyk et al, 2006) have shown that complex optical responses can be obtained from periodic and nonperiodic arrays of MWCNTs as a result of controlling the geometry and spacing of the arrays, so that it is possible to create structures that respond very strongly to specific wavelengths or bands of wavelength. Finely tuned detectors that can respond to predetermined wavelength bands ranging from the ultraviolet to the infrared region.…”
Section: A Case Study -Flying At 0001c and Beyondmentioning
confidence: 99%
“…These studies have revealed the manner in which the optical properties are related to nanotube and array geometries. [1][2][3][4] Periodic CNT arrays exhibit Bragg diffraction, 5 photonic bandgap properties, 6 and plasmonic resonance. Nonperiodic CNT arrays interact with light waves similarly to the way in which radio antennae interact with radio waves.…”
mentioning
confidence: 99%